2001
DOI: 10.21091/mppa.2001.3015
|View full text |Cite
|
Sign up to set email alerts
|

A Personality Profile of Professional and Conservatory Student Dancers

Abstract: The Test of Attentional and Interpersonal Style (TAIS), a 144-item personality inventory developed by sport psychologist Robert Nideffer, was used for the first time with dancers in this study to explore (1) what it would divulge about the shared personality traits of elite-level dancers and (2) whether it might be useful as a teaching/counseling tool to enhance the performance of under-achieving dance students. Two sets of subjects were tested: group 1 (n = 41: 22 females, 19 males) was composed of professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Moreover, dancers seem generally to have low confidence and possess little knowledge related to how to manage their careers and increase their quality of life (Hoffer, 1981;van Staden et al, 2009;Haraldsen et al, 2021a). Yet, studies indicated that the dancers' life quality could increase if measures, such as psychological skills training and psycho-education, were systematically applied in their education and professional life (Redding and Quested, 2006;Solomon et al, 2002;Diaz et al, 2008;van Staden et al, 2009;Klockare et al, 2011;Carattini, 2020;Kim et al, 2022). So far, positive outcome evidence appeared dispersed and lack coherence, which made it difficult to detect an overall prevalence.…”
Section: Positive Outcomes (53)mentioning
confidence: 99%
“…Moreover, dancers seem generally to have low confidence and possess little knowledge related to how to manage their careers and increase their quality of life (Hoffer, 1981;van Staden et al, 2009;Haraldsen et al, 2021a). Yet, studies indicated that the dancers' life quality could increase if measures, such as psychological skills training and psycho-education, were systematically applied in their education and professional life (Redding and Quested, 2006;Solomon et al, 2002;Diaz et al, 2008;van Staden et al, 2009;Klockare et al, 2011;Carattini, 2020;Kim et al, 2022). So far, positive outcome evidence appeared dispersed and lack coherence, which made it difficult to detect an overall prevalence.…”
Section: Positive Outcomes (53)mentioning
confidence: 99%
“…Solomon and Solomon suggested that sport psychologist Robert Nideffer's Test of Attentional and Interpersonal Styles, widely recognized for its validity and reliability as a means of helping underachieving athletes to realize their potential, might profitably be put to the same use with troubled dancers. 75,76 Our psycho-educational model, to which we now turn our attention, represents another step toward acknowledging and dealing with the fact that some aspiring dancers are incapable of adjusting on their own to the realities of dance training and performance at the vocational level.…”
Section: Part Two: a Psycho-educational Modelmentioning
confidence: 99%
“…This can include costs such as those from insurance claims, Workers Compensation, treatment, rehabilitation, re-casting, and re-rehearsing, among others. 7,8 In addition to the physical complaints, pain, and high stress resulting from their injuries, the affected dancers even risk termination of their careers.…”
Section: Introductionmentioning
confidence: 99%